Study of Biopharmaceutical Agricultural Development in Karanganyar Regency - Pinandhito, Gregorius Purusatama Ritang; Nuriawati, Nita; Rahmawati; Dianafi, Dani Rizky; Wirawati, Dayang Kalih Shafira; Mayori, Indriya Mardiana; Syakira, Najla Alifa; Arianto, Nurul Fauziah; Pratama, Rizky Aditya; Cahyani, Shilla Dewanti Ayu; Nchimunya, Nachilime (Perencanaan Wilayah dan Kota FT UB, 2023)
Agriculture in Karanganyar Regency is not considered a primary sector in the Solo Raya area; however, it possesses untapped potential that needs to be developed. Medicinal plants, or bio-pharmaceutical commodities, are among the prominent potentials, with Karanganyar Regency ranking among the top 10 highest producers in Central Java Province and having seven sub-districts as centres for medicinal plant cultivation. Ginger, turmeric, and galangal are outstanding commodities in the Agricultural Region of Karanganyar, identified as potential and key commodities based on linkage system analysis, agropolitan subsystem analysis, spatial structure analysis, LQ and shiftshare analysis, policy analysis, and land carrying capacity analysis. The analysis reveals the presence of potential and challenges as driving and inhibiting factors. Nevertheless, the bio-pharmaceutical agriculture sector faces several issues, such as inadequate support in terms of facilities and infrastructure, as well as imbalances in inter-regional infrastructure conditions that impact marketing disparities. Additionally, monitoring and reporting of agricultural sector development programs are not yet optimal. Therefore, further analysis and studies are needed to develop the agricultural sector, particularly in the bio-pharmaceutical commodities domain.